Population Genetic Structure of Citrus Tatter Leaf Virus in Zhejiang Province, China - Lianming Lu; Shunmin Liu; Zhanxu Pu; Baoju An; Danchao Du; Xiurong Hu; Jia Lv; Zhendong Huang (Viruses)
Citrus tatter leaf virus (CTLV), a major pathogen threatening global citrus production, remains poorly characterized in terms of its regional genetic diversity and evolutionary dynamics. To address this gap, we conducted a comprehensive population genetic analysis of CTLV in Zhejiang Province, China, using 181 coat protein (CP) gene sequences—the largest regional CTLV dataset to date. Our analyses uncovered substantial genetic diversity among Zhejiang CTLV isolates. Phylogenetic reconstructions revealed that these isolates span multiple clades, closely aligning with global CTLV population structures, indicative of recurrent viral introductions and extensive regional circulation. Population structure analyses revealed significant genetic differentiation driven by geography, with Jinhua isolates forming a distinct cluster, and by host species, with Citrus reticulata ‘Criton’ isolates diverging from those in other citrus varieties. Selection pressure analysis indicated that while most CP polymorphic sites were under purifying selection, several clade-specific codons showed signatures of positive selection. These results offer new insights into CTLV’s population structure and localized evolutionary trajectories, enhancing our understanding of its regional adaptation and informing strategies for disease management and control of this globally significant pathogen.